Penerapan Model Pembelajaran Project Based Learning Pembuatan Busana Industri (Grading Rok) untuk Meningkatkan Hasil Belajar Siswa Kelas XI Tata Busana SMK Negeri 3 Pamekasan - Irmaniar Dwi Yuliana Putri; Marniati Marniati; Peppy Mayasari; Mita Yuniati (Universitas Palangka Raya, 2024)
Project based learning is a learning method that uses projects/activities as media. Students carry out exploration, assessment, interpretation, synthesis and information to produce various forms of learning outcomes. The objectives of this research are (1) To determine the application of the project based learning model to making skirt grading patterns, (2) To determine the response of class XI students at SMK Negeri 3 Pamekasan to learning to make skirt grading patterns using the project based learning method, (3) To find out the learning outcomes of class XI students at SMK Negeri 3 Pamekasan after implementing learning using the project based learning method in making skirt grading patterns. The type of research applied is classroom action research (CAR). The research was conducted at SMK Negeri 3 Pamekasan with 31 students in class XI Fashion Design 1 consisting of 30 women and 1 boy. Class XI Fashion Design 2 has 34 students consisting of 34 women and 0 men at SMK Negeri 3 Pamekasan. The data collection methods used were (1) observation, (2) student learning outcomes tests. The research instruments used were (1) observation sheet, (2) test sheet. The data analysis technique uses quantitative descriptive analysis. The research results showed (1) Teacher activity in cycle 1 obtained a score of (70.6%) and experienced an increase in cycle 2 (82.9%) which was very good, (2) student activity in cycle 1 obtained a score of (70.8%) and experienced an increase in cycle 2 (83.8%), the increase in score was declared successful, (3) Student learning outcomes in cognitive, affective and psychomotor assessments from cycle 1 to cycle 2 experienced an increase with the completeness score reaching a total of (97%) which can be categorized as very good.